Advanced Implant-Prosthetic Rehabilitation: How to Obtain a Correct Restoration of Both Functions and Aesthetics in Patients with Complex Combined Dental and Maxillofacial Trauma: A Case Report and Topical Review of the Literature - M. M. Figliuzzi; A. Giudice; L. Fortunato (Case Reports in Dentistry)
Aim. This study aims to explain the main steps that characterize the implant-prosthetic rehabilitation in complex combined dental and maxillofacial trauma. Material and Methods. A 20-year-old patient reported an extensive facial trauma which also involved the alveolar process of the maxillary bone. The patient reported a maxillofacial fracture and the loss of teeth 1.3, 1.2, 1.1, and 2.1. A “Le Fort” type 2 fracture was also reported, with the malar bone involvement. After reduction and containment of bone fractures, through appropriate mounting plates, appropriate functional and aesthetic rehabilitation of the patient were replaced thanks to a temporary removable prosthesis. After 6 months, the patient performed numerous clinical investigations, aimed at a proper planning of implant-prosthetic rehabilitation of the upper dental arch. Conclusion. With the planning of the case, as well as respecting the surrounding biological structures, the surgery of implants can be carried out with the most appropriate procedure. Lastly, new dental implants with highly bioactive surfaces have been developed, providing an excellent and rapid bone integration.